Facilitators and barriers to effective supervision of maternal and newborn care: a qualitative study from Shinyanga region, Tanzania - Tumaini Mwita Nyamhanga; Gasto Frumence; Anna-Karin Hurtig (Taylor & Francis Group, 2021)
Background: Despite routine supportive supervision of health service delivery, maternal and newborn outcomes have remained poor in sub-Saharan Africa in general and in Tanzania in particular. There is limited research evidence on factors limiting the effectiveness of supportive supervision in improving the quality of maternal and newborn care. Objective: This study explored enablers of and barriers to supportive supervision in maternal and newborn care at the district and hospital levels in Shinyanga region in Tanzania. Methods: This study employed a qualitative case study design. A purposeful sampling approach was employed to recruit a stratified sample of health system actors: members of the council health management team (CHMT), members of health facility management teams (HMTs), heads of units in the maternity department and health workers. Results: This study identified several barriers to the effectiveness of supportive supervision. First, the lack of a clear policy on supportive supervision. Despite the general acknowledgement of supportive supervision as a managerial mechanism for quality improvement at the district and lower-level health facilities, there is no clear policy guiding it. Second, limitations in measurement of progress in quality improvement; although supportive supervision is routinely conducted to improve maternal and newborn outcomes, efforts to measure progress are limited due to shortfalls in the setting of goals and targets, as well as gaps in M&E. Third, resource constraints and low motivation; that is, the shortage of resources - CHMT supervisors, health staff and funds - results in irregular supervision and low motivation. Conclusion: Besides resource constraints, lack of clear policies and limitations related to progress measurement impair the effectiveness of supportive supervision in improving maternal and newborn outcomes. There is a need to reform supportive supervision so that it aids and measures progress not only at the district but also at the health facility level.